Incorporating chemical shrinkage volume into Gibson’s solution - Walske, Megan; Doherty, J. (NRC Research Press, 2018)
Rapid filling of low-permeability cemented paste backfill (CPB) into underground stopes results in the generation of significant excess pore pressures. These are dissipated through conventional consolidation and shrinkage due to cement hydration. Gibson’s solution for excess pore pressures in an accreting sediment can be used to assess the self-weight consolidation of CPB in a stope. In this paper, numerical modelling is used to determine the chemical shrinkage-induced pore pressure response for hydration of CPB for an accreting material and the results presented in a series of dimensionless design charts. It is shown that superposition can be used to combine Gibson’s solution with the newly developed charts for chemical shrinkage- induced pore pressures. This allows a qualitative assessment of potential pore pressure development in a CPB backfilled stope.